Incidence and Severity of Concussions Among Young Soccer Players Based on Age, Sex, and Player Position. Issue 1 (13th January 2022) - Weiner, Alden R.; Durbin, John R.; Lunardi, Susie R.; Li, Adam Y.; Hannah, Theodore C.; Schupper, Alexander J.; Gal, Jonathan S.; Jumreornvong, Oranicha; Spiera, Zachary; Ali, Muhammad; Marayati, Naoum Fares; Gometz, Alex; et al.
Background: Previously studied risk factors for sports-related concussion in soccer players include sex, age, and player position. However, prior studies were limited in number, they reported conflicting results, and most did not assess initial concussion severity. Purpose/Hypothesis: The purpose of this study was to conduct an in-depth analysis of soccer players across key demographic groups (sex, age, position) for both concussion incidence and severity. It was hypothesized that concussion incidence and severity would be higher among male players, players aged ≥17 years, and goalkeepers. Study Design: Cohort study; Level of evidence, 3. Methods: The authors analyzed baseline and postinjury ImPACT (Immediate Post-Concussion Assessment and Cognitive Testing) scores for athletes aged 12 to 22 years between July 2009 and June 2019. Players were assigned to an age group based on when they had their most recent baseline test. Concussion incidence and concussion severity index were compared using t tests and multivariate logistic regression. Results: For 1189 individuals who reported soccer as their primary sport, 1032 contributed 1754 baseline ImPACT tests (some individuals had multiple baseline tests), whereas 445 individuals were suspected of sustaining a concussion and then referred for a postinjury 1 test. Of these players, 254 (24.6%) had both a baseline and a postinjury test and were analyzed for concussion severity. Linear regression showed that forwards had a lower incidence of ImPACT-proxied concussions than goalkeepers had ( P = .008). Female players had a significantly higher incidence of ImPACT concussions compared with male players (mean, 0.07 [female] vs 0.04 [male] concussions per person-year; P = .05). Players in the ≥17-year age group had a higher incidence of ImPACT concussions than players in the 15- to 16-year age group ( P = .04), although the 15- to 16-year age group had more severe concussions than the ≥17-year age group (mean severity index, 2.91 [age 15-16 years] vs 1.73 [age ≥17 years]; P = .001). Conclusion: Female soccer players experienced a higher incidence of concussion than did male players, and goalkeepers experienced a greater incidence of ImPACT concussions than did forwards. Players of both sexes and all positions in the 15- to 16-year age group showed increased initial concussion severity compared with the ≥17-year age group, despite a lower comparative incidence of ImPACT concussions. Further study is needed to understand whether sex and player position affect concussion severity.